Estudio de factibilidad técnica y financiera para la constitución de una empresa dedicada a la prestación de servicio de aseo en la ciudad de Neiva a través de una aplicación móvil. - Quintero Polanía, Yenifer Andrea; Paredes Vargas, Silvia Patricia (Corporación Universitaria Minuto de Dios, 2020)
El presente proyecto estudia la factibilidad técnica y financiera para la constitución de una empresa dedicada a la prestación de servicio de aseo en la ciudad de Neiva a través de una aplicación móvil. Dicha idea de negocio surge al observar que ese mercado se encuentra actualmente sin explorar a nivel regional y poco a nivel país. Si hablamos del servicio doméstico se encontró que en el Huila y Neiva se contrata de manera presencial y/o telefónico, con referidos de conocidos y muchas veces de manera informal, lo que dificulta que el servicio se preste con calidad y seguridad. Las familias de la actualidad se encuentran conformadas en su mayoría por padres jóvenes en donde los dos ejercen alguna actividad económica ya sea empleados o trabajadores independientes y no cuentan con el tiempo para llevar acabo las labores de limpieza en su hogar, por lo que surge la necesidad de contratar el servicio doméstico ya sea por días o por mes. En la ciudad de Neiva el servicio no es conocido, puesto que los hogares deben correr con los gastos y responsabilidades de contar con una operaria domestica al mes, y en el caso de que el servicio se preste por días, deben asumir riesgos al ingresar una persona desconocida a su vivienda, en la mayoría de las veces las operarias son referidas de personas conocidas, pero esta labor dificulta contratar el servicio oportunamente.Por tal motivo surge la idea de prestar el servicio de aseo domestico por medio de una empresa que genere confianza, seguridad, calidad y que adicionalmente contratarlo se realice fácil y rápido por medio de una plataforma digital “Aplicación móvil”. La era actual de la digitalización y el crecimiento exponencial del uso de aplicaciones móviles en tiempos de Covid-19 favorecen a que el proyecto tenga buena acogida por parte del mercado actual.

The project is framed in the activity of general services and with an added value that it works under a technological platform, this leads to being immersed in the digital age and with the favorability that today the largest population has tools such as a pc or cell phone where you can access the services that En Tus Manos SAS will provide, the service is outlined for those customers who do not have the time to perform household cleaning tasks in strata 3,4,5 and 6. In their Most are people who work and that these tasks are not among their priorities, but they do demand the need to keep their homes neat and orderly, among them are employees, entrepreneurs and independent workers. Likewise, there is a social responsibility to include women heads of households in the hiring of workers' personnel in order to contribute to these ladies to legalization and a dignified working life, with the opportunity to have a formal job, and in In order to contribute to the decrease in unemployment of women, which for the department of Huila according to DANE for the year 2017 corresponded to 57.4, while in men the percentage was 42.6. It was found that the market is not exploited, so it is an opportunity that En Tus Manos SAS has to explore it, likewise it has had a favorable advantage with the growth of the construction sector that generates the possibility of new homes that the company it can attend, since the construction of at least 33,000 homes is planned in the next 34 years; which implies the construction of approximately 1,000 homes per year, hoping to access 2% of that growing market, however, initially it is intended to obtain a share of the current market, there are around 20,647 homes that are located in stratum 3, 4,5 and 6 middle, upper-middle and upper class households, of which, according to the sample, 25% make use of the toilet service and 7.5% do it virtually, which means that an optimistic scenario can be proposed and cover a range of 380 houses per month. The main competitor is the service provided by the operators informally, with person-to-person references, since the company with the same characterization of the service that it wants to provide was not identified in the investigation. The results in accordance with the investment and financing plan, showed that the feasibility is favorable for the starting scenario with 220 monthly households, presenting an IRR of 49%, which represents a profitability since it is> 0 with a Net Present Value of $ 254,812,891 pesos for the five years. To reach the breakeven point, 4,004 households need to be served, which takes 282 days to reach it. In the optimistic scenario, it is calculated on 380 households per month, presenting an IRR of 50.5%, which represents an excellent profitability, with a Net Present Value of $ 257,822,630 pesos for the five years. To reach the breakeven point, 3,985 households need to be served, which takes 281 days to reach it. In the pessimistic scenario, it is calculated on 158 monthly households, presenting a negative IRR which represents a loss for the investment to be made, with a Net Present Value of $ 29,480,964 pesos for the five years. To reach the equilibrium point, 2,148 households need to be served, which takes 368 days to reach it.
Desarrollar un estudio de factibilidad técnica y financiera para la constitución de una empresa dedicada a la prestación de servicio de aseo en la ciudad de Neiva a través de una aplicación móvil.
Keywords: Servicio doméstico; Factibilidad; Aplicación movil; Empresa de aseo; Aplicación móvil; Estudio de factibilidad